EMI filter design to improve electromagnetic immunity of hearing aid devices - Agustiar (2013)
Electromagnetic interference (EMI) from mobile phones on hearing aids are investigated. Different operating modes of the hearing aid have different impact on the immunity of the device. An experimental study will be carried out to understand the impact of EMI filter on the compliance of the hearing aid under the operating modes.